INSTRUCTIONS FOR CREATING A STEP-BY-STEP PIT DESIGN IN MINING ENTERPRISES - Rashanov Zavqiddin Yahyo o'g'li,; Barotov Vasliddin Nusrat o‘g‘li,; Ergasheva Zulxumor Abdaaliyevna,; Zaytova Madina Nazarbay qizi, (International Journal of Innovations in Engineering Research and Technology, 2023)
One of the main problems of open-pit mining is the efficient use of freight transportation (freight turnover) and transportation fleet. for maximum efficiency and minimum costs, after extracting minerals, we need to transport them to areas as close as possible to the mining enterprise's border area. Shovels and trucks are the most common are widely used loading and transportation equipment in open pit mining around the world. The the problem is difficult because the truck and shovel systems are complicated by uncertainties related to truck and shovel operations and numerous parameters and as a result problem-related interactions should be considered. This paper develops and implements a stochastic discrete-event simulation model to design and analyze the behavior of a truck and shovel handling system. The boundary area of the mine along with short-term plans, guidelines for open pit mining were given. This model simulates a complex system of trucks and shovels and takes into account the uncertainties associated with the operation of trucks and shovels. This ensures that operating plans are consistent with net present value and ensures that the planning stage is more perfect. Two main subproblems are addressed in this study. First of all, equipment a selection problem in which the number of trucks and shovels is determined. In the second subproblem, key performance indicators using the resources identified in the previous step truck and shovel system is evaluated. Optimal short-term production at both stages the table is the main input in the model. Developed using the proposed simulation model simulation software and it is applied in a real open pit iron ore mine. Several research processes for location planning of mining enterprises are presented as examples.